2020
DOI: 10.1111/eufm.12252
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CEO compensation under large and small institutional ownership

Abstract: I examine the influence of large and small institutional investors on different components of chief executive officer (CEO) compensation, using US data for 2006–2015. An increase in large institutional ownership reduces total pay and current incentive compensation (i.e., options, stocks, bonus pay), whereas small institutional investors lower long‐term incentive pay (i.e., pension, deferred pay, stock incentive pay). These findings are consistent with managerial agency theory and the substitution of incentive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
7
1
Order By: Relevance
“…However, the coefficient is not significant in the case of TC, and therefore, much cannot be established based on these estimates. In line with this, Gill (2014) and Tosun (2019) found an insignificant impact of BSZE on total pay. Alves et al (2016) also found a negative but insignificant effect of BSZE on the CEO’s total earnings.…”
Section: Analysis and Findingssupporting
confidence: 64%
See 2 more Smart Citations
“…However, the coefficient is not significant in the case of TC, and therefore, much cannot be established based on these estimates. In line with this, Gill (2014) and Tosun (2019) found an insignificant impact of BSZE on total pay. Alves et al (2016) also found a negative but insignificant effect of BSZE on the CEO’s total earnings.…”
Section: Analysis and Findingssupporting
confidence: 64%
“…For the purpose of the present study, CEO COMP is the dependent variable measured through cash compensation and total compensation, which includes cash as well as non-cash components of pay based on prior literature (Almazan et al , 2005; Ozkan, 2011; Sheikh et al , 2017; Tosun, 2019). The independent variable consists of two sets of variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our second set of corporate governance variables, we include a set of CEO‐related control variables considering the influence of institutional investors on the CEO (e.g., Tosun, 2020). These variables include Duality , which is an indicator that equals one if the CEO is also the chair of the board and zero otherwise; CEOTenure , which is the number of years the CEO has held that title in that firm; and CEOOwn , the fraction of outstanding shares owned by the CEO.…”
Section: Robustness Testsmentioning
confidence: 99%
“…In our second set of corporate governance variables, we include a set of CEO-related control variables considering the influence of institutional investors on the CEO (e.g., Tosun, 2020). These variables include Duality, which is an indicator that equals one if the CEO is also the chair of the board and zero otherwise; CEOTenure, which is the number of years the CEO has held that title in that firm; and CEOOwn, the fraction of outstanding shares owned by the CEO.…”
Section: T a B L E 6 Additional Controls-managerial Learningmentioning
confidence: 99%